Pengembangan Lembar Kegiatan Peserta Didik berbasis Project Based Learning pada Materi Komposisi Bangun Datar Kelas 4 Sekolah Dasar - Cahyaningtyas, Aura; Arifin, Bustanol; Deviana, Tyas (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
The purpose of this study is to develop a project-based learning activity sheet (PBLA) to reinforce the learning of content related to the construction of plane figures in mathematics classes. The study was conducted in Gianti Sidoarjo's Class IV SDN 1 with a sample of 10 students. The ADDIE model was used as the design method. The validators of the study were experts in teaching materials and LCAP. The data collected were qualitative and quantitative. Observation, interview, questionnaire, survey, and documentation methods were used to collect data. Pre-tests and post-tests were administered in the sample class. The analysis of the data yielded the following data: (1) the results of the material test were good (70.0%); (2) the results of the LCAP test were good (80.75%); (3) according to the responses to the questionnaire, the appearance, motivational qualities, and usefulness in the learning process were acceptable for all students; (4) the learning results were good (0.8). Thus, the conclusion of this study is that the Project-Based Learning Activity Sheet (PBLA) is highly rated, suitable as teaching material for SR Class IV, and furthermore, can improve students' learning outcomes.